Detecting multi-scale distance-based inconsistencies in cities through complex-networks - Spadon, Gabriel; Brandoli, Bruno; Eler, Danilo M. [UNESP]; Rodrigues-, Jose F. (Elsevier B.V., 2019)
We propose an algebraic tool-set and related algorithms to track access problems not obviously observed in urban environments represented as street mashes. Our tool-set assumes that points of interest must be promptly accessible within the paths of a street network. Over that assumption, we introduce formalisms and computational tools to detect and evaluate access-related problems. The output of our methods, in the form of inconsistent nodes found in a given city, has the potential to assist the decision-making process regarding the positioning of resources, building of new services, and outlining the initial design of a city. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Complex network; Network analysis; Urban structure